2009
DOI: 10.4161/chan.3.2.8037
|View full text |Cite
|
Sign up to set email alerts
|

The N-type calcium channel is a novel target for treating alcohol use disorders

Abstract: Channels 77 N-type calcium channels as therapeutic targets for alcoholism [Channels 3:2, 77-81; March/April 2009]; ©2009 Landes BioscienceWe recently validated the N-type calcium channel as a target for the treatment of alcoholism and anxiety. N-type calcium channels are neuronal presynaptic ion channels that regulate neurotransmitter release at many sites in the brain. Mice lacking N-type calcium channels exhibit reduced ethanol consumption and show resistance to the acute intoxicating effects of ethanol. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The remaining significant pathways in brain revolved around members involved with glutamatergic, calcium and G-protein signaling. Pharmacological inhibition of the N-type voltage gated calcium channel Ca v 2.2 ( Cacna1b ) results in reduced ethanol intoxication, reinforcement, and reward in mice (Newton and Messing, 2009). Kcnj5 , the G βγ -activated inward rectifying potassium channel 4 (GIRK4) contains a binding site for and is activated by ethanol (Aryal et al, 2009), and is necessary for ethanol–induced conditioned place preference in mice (Tipps et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining significant pathways in brain revolved around members involved with glutamatergic, calcium and G-protein signaling. Pharmacological inhibition of the N-type voltage gated calcium channel Ca v 2.2 ( Cacna1b ) results in reduced ethanol intoxication, reinforcement, and reward in mice (Newton and Messing, 2009). Kcnj5 , the G βγ -activated inward rectifying potassium channel 4 (GIRK4) contains a binding site for and is activated by ethanol (Aryal et al, 2009), and is necessary for ethanol–induced conditioned place preference in mice (Tipps et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this paradigm, Cav1.3 appears to be the most relevant channel (N'gouemo et al, 2015); however, the paradigm is very different from our model of alcohol dependence as well as the brain regions analyzed. Furthermore, there are reports depicting a role of non-LTCCs, that is, N-type (Newton et al, 2008;Newton and Messing, 2009) and T-type calcium channels (Carden et al, 2006;Nordskog et al, 2006), in alcohol-related behavior. Therefore, we analyzed the expression of P/Q-type, N-type, and T-type non-LTCCs in 3-week abstinent rats by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the vascular, neurovegetative, and neurotransmitter release effects of ACh are mediated by the N‐type calcium channel. The N‐ and T‐type voltage‐gated calcium channel blockers have recently been used in psychiatry to treat disorders such as ethanol addiction (45,46). The proposed psychiatric effects of this class of drugs are inapplicable in our study; none of our patients reported ethanol abuse.…”
Section: Discussionmentioning
confidence: 58%